2020
DOI: 10.1002/ctm2.5
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces fatty liver disease in breast cancer through the MAPK8/FoxO pathway

Abstract: Background Prevention of metabolic complications of long‐term adjuvant endocrine therapy in breast cancers remained a challenge. We aimed to investigate the molecular mechanism in the development of tamoxifen (TAM)‐induced fatty liver in both estrogen receptor (ER)‐positive and ER‐negative breast cancer. Methods and results First, the direct protein targets (DPTs) of TAM were identified using DrugBank5.1.7. We found that mitogen‐activated protein kinase 8 (MAPK8) was one DPT of TAM. We identified significant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The obviously changed genes were mainly related to the MAPK signaling pathway ( mycb and gadd45ba ), Fox O signaling pathway ( rag1 , cdkn1a , and gadd45ba ), cell cycle ( mycb , cdkn1a , and gadd45ba ), and apoptosis ( gadd45ba ) (Figure C). Similar to our results, a previous study reported that the inhibition of MAPK signaling pathways caused disturbance of the FoxO signaling pathway and finally led to cell cycle arrest and apoptosis in pancreatic cancer cells. , Notably, gadd45ba was identified as the hub gene within the above-mentioned signaling pathways, followed by cdkn1a and mycb . The Gadd45 family of proteins has been shown to be a sensitive stress sensor for various physiological and environmental pollutants .…”
Section: Resultssupporting
confidence: 91%
“…The obviously changed genes were mainly related to the MAPK signaling pathway ( mycb and gadd45ba ), Fox O signaling pathway ( rag1 , cdkn1a , and gadd45ba ), cell cycle ( mycb , cdkn1a , and gadd45ba ), and apoptosis ( gadd45ba ) (Figure C). Similar to our results, a previous study reported that the inhibition of MAPK signaling pathways caused disturbance of the FoxO signaling pathway and finally led to cell cycle arrest and apoptosis in pancreatic cancer cells. , Notably, gadd45ba was identified as the hub gene within the above-mentioned signaling pathways, followed by cdkn1a and mycb . The Gadd45 family of proteins has been shown to be a sensitive stress sensor for various physiological and environmental pollutants .…”
Section: Resultssupporting
confidence: 91%
“…And, these pathways have crosstalk with other common cancer pathways ( Chen and Wang, 2012 ; Sato, 2013 ). For example, Pathways in cancer, Focal adhesion ( Ocak et al, 2010 ; Gari et al, 2016 ; Gu et al, 2018 ; Gong et al, 2019 ), Cell cycle, FoxO signaling pathway ( Mohd et al, 2017 ; Gong et al, 2020 ), Choline metabolism in cancer, Oxytocin signaling pathway ( Cassoni et al, 1994 ; Pequeux, 2002 ; Wang et al, 2020 ), ErbB signaling pathway ( Liu et al, 2008 ; Aline et al, 2015 ), and JAK-STAT signaling pathway ( Hernández-Vargas et al, 2011 ; Wang et al, 2018 ; Na and Balko, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Functional analysis of candidate DE-miRNAs and DE-mRNAs selected from TCGA and GEO databases revealed that they were related to the classic p53, FoxO, TGF-beta, and hippo pathways, consistent with previous studies. 19 , 20 , 21 , 22 KEGG pathway analysis of proteoglycans in cancer has attracted increasing attention. Proteoglycans affect malignant cells and the tumor microenvironment in both solid and hematopoietic cancers.…”
Section: Discussionmentioning
confidence: 99%